Analisis Tingkat Kesehatan Finansial Pada Koperasi Simpan Pinjam CU Makmur Bersama Kota Tebing Tinggi - Hutauruk, Rapat Piter Sony (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
This study aims to analyze the financial health level of the Credit Union (CU) Makmur Bersama Savings and Loan Cooperative in Tebing Tinggi during the 2019-2021 period. This assessment is important to determine the cooperative’s ability to maintain performance and adhere to sound financial management principles. The research uses a qualitative method with a descriptive approach by analyzing secondary data in the form of financial reports, specifically balance sheets and income statements from 2019 to 2021. Data collection was conducted using documentation techniques. The data were analyzed using financial ratio analysis based on six indicators of cooperative health: capital, quality of productive assets, efficiency, liquidity, independence and growth, and cooperative identity, referring to the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and SMEs of the Republic of Indonesia No. 06/Per/Dep.06/IV/2016. The results showed that CU Makmur Bersama was in a healthy category throughout the observed period with an average score of 71.83. These findings are expected to serve as a basis for improving and strengthening the cooperative’s financial management system to ensure its sustainability and member welfare.